Nanogapped impedimetric immunosensor for the detection of 16 kDa heat shock protein against Mycobacterium tuberculosis - Subash C. B. Gopinath; Veeradasan Perumal; Ramanujam Kumaresan; Thangavel Lakshmipriya; Haarindraprasad Rajintraprasad; Balakrishnan S. Rao; M. K. Md Arshad; Yeng Chen; Norito Kotani; Uda Hashim (Springer, 2024)
Microchimica Acta volume 183, pages2697–2703 (2016)